Struggling in the Street and at the Table. Issue 2 (April 2015) - Roy, Beth; Burdick, John
<x xml:space="preserve">Abstract</x> Two scholar practitioners of conflict intervention and social movements present case histories of mediated conflicts involving complex choreographies of contention and negotiation. Both processes, while differently structured and facilitated, have led to improvements in the dynamics of identity‐based conflicts in urban communities. The authors raise theoretical questions and propose improvements to practice.